Evaluation Of The Implementation Of The Alfamidi Industry Work Practices Program For Alfamidi Class Students Of Smk Negeri 1 Malang - Agustina, Dedek; Wedi, Agus; Ulfa, Saida (Universitas Negeri Malang, 2024)
Evaluation of the Implementation of the Industrial Work Practice Program (Prakerin) for Alfamidi Class Students at SMK Negeri 1 Malang is a comprehensive program evaluation of Reaction to assess student satisfaction, Learning to assess students' mastery of knowledge of the material, Behavior, industrial colleagues' assessment of student attitudes, and the final results of student achievements. on student competencies determined by industry and schools. Evaluation from various aspects provides an assessment that represents each important element in a program. This research uses descriptive quantitative methods, the data obtained is data that describes actual phenomena in the field. The data in this research were obtained from the results of distributing questionnaires to 63 student respondents, and 35 industrial supervisors for each shop, as well as 2 teacher supervisors. Data from these aspects obtained on average is classified as very good. Although in this study there were also 12% of the sample classified